2010
DOI: 10.1002/gps.2612
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of neuropsychological function to instrumental activities of daily living in mild cognitive impairment

Abstract: Having more difficulties in IADL, especially those with higher demand on cognitive capacities, was found to be associated with MCI and overall cognitive functioning. This has implications for the definition of MCI, as lack of functional impairment is generally used as a criterion for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 34 publications
11
125
0
1
Order By: Relevance
“…These specific functional deficits according to different cognitive status appeared only in selective tasks, which is consistent with previous results [5,26,27]. In our study, shopping and bathing were significant discriminators between A-MCI and throughout the cognitive spectrum spanning from NCI, SCI, to NA-MCI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These specific functional deficits according to different cognitive status appeared only in selective tasks, which is consistent with previous results [5,26,27]. In our study, shopping and bathing were significant discriminators between A-MCI and throughout the cognitive spectrum spanning from NCI, SCI, to NA-MCI.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, shopping and bathing were significant discriminators between A-MCI and throughout the cognitive spectrum spanning from NCI, SCI, to NA-MCI. These results were unexpected, since shopping and personal hygiene, such as bathing, are categorized as items requiring low cognitive demand [26]. Earlier studies have obtained inconsistent results for shopping.…”
Section: Discussionmentioning
confidence: 64%
“…By asking about both the patients' and the relatives' perceptions of everyday problems, we can get a better picture of the problems occurring in occupational performance, which helps us to plan relevant interventions. As the literature shows, lower cognition is associated with more difficulties in IADL and people can have difficulties in daily life even in MCI (Reppermund et al, 2011). This instrument will hopefully be helpful in capturing these difficulties.…”
Section: Main Findingsmentioning
confidence: 95%
“…In the dementia and geriatric literature, the ability to perform ADL is often referred to as functional ability and as a measurement of disability (Abhilash et al, 2004, Reppermund et al, 2011. Dementia affects people's ability to perform activities of daily life, initially in complex activities but progressing to more basic activities such as the ability to cope with dressing and toileting later in the disease course (Armanius Björlin et al, 2004).…”
Section: Cognition In Relation To Adlmentioning
confidence: 99%
“…1 49) . Some studies focused on mild cognitive impairment (MCI) and said that older people with MCI had difficulty performing their IADLs [50][51][52][53] . Azuchi's longitudinal study on Japanese community-dwelling elderly persons, aged 65 years and older, found a significantly greater risk (a factor increase of 2.4 -9.4) among individuals with MCI of losing their ability to perform ADL and IADL compared to those with intact cognition 54) .…”
Section: Activities Of Daily Life (Adl) and Instrumental Activities Omentioning
confidence: 99%